2016
DOI: 10.5664/jcsm.5568
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reporting by Unsafe Drivers Is, with Education, More Effective than Mandatory Reporting by Doctors

Abstract: Study Objectives: Health professionals are frequently required to report to relevant authorities all drivers who are potentially unsafe due to medical conditions. We aimed to assess both the effect of mandatory reporting (MR) on patient self-predicted behavior and what factors might encourage unsafe drivers to self-report to these authorities. Methods: We included 5 questions in the South Australian Health Omnibus Survey, an annual, community based, face-to-face survey. We asked (1) how subjects would behave t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Again substantiating their warning, our study showed that the majority of doctors suspected some of their patients of attempting to doctor shop (25/35), discouraging others from seeking medical help (23/35) and withholding information (33/35) because of the fear of MR leading to loss of licence. Given that between 5 and 20 out of 35 doctors ‘frequently’ suspected patients of these behaviours, these results lend weight to our voiced suspicion that our previously reported figure of 9% of the population who reported being likely to behave in an unsafe manner if their licence was at risk was an underestimation …”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…Again substantiating their warning, our study showed that the majority of doctors suspected some of their patients of attempting to doctor shop (25/35), discouraging others from seeking medical help (23/35) and withholding information (33/35) because of the fear of MR leading to loss of licence. Given that between 5 and 20 out of 35 doctors ‘frequently’ suspected patients of these behaviours, these results lend weight to our voiced suspicion that our previously reported figure of 9% of the population who reported being likely to behave in an unsafe manner if their licence was at risk was an underestimation …”
Section: Discussionmentioning
confidence: 58%
“…Given that between 5 and 20 out of 35 doctors 'frequently' suspected patients of these behaviours, these results lend weight to our voiced suspicion that our previously reported figure of 9% of the population who reported being likely to behave in an unsafe manner if their licence was at risk was an underestimation. 9 Our earlier research also highlighted the importance of the legal obligation of patients to self-report to the DPTI when their health may affect their ability to operate a motor vehicle safely. Concurrent with MR, selfreporting provides an alternative and possibly superior pathway.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This issue of JCSM includes a provocative paper by Elgar et al 1 that has implications for all of us who drive. These investigators analyzed responses of more than 3,000 individuals from the face-to-face South Australian Health Omnibus Survey, and concluded that 9% would avoid diagnosis, lie to their doctor or doctor shop in order to keep their license.…”
mentioning
confidence: 99%